Preparation process of sodium ion battery taking 2H phenazine polymer as positive electrode material
By using 2H phenazine polymer as the positive electrode material of sodium ion batteries and combining the assembly process of conductive agents and binders, the application problems of 2H phenazine in sodium ion batteries and environmental pollution problems are solved, and efficient electrochemical performance and resource recycling are achieved.
Patent Information
- Application Number
- CN202411831215.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is unclear whether 2H phenazine redox polymers can be used as a positive electrode material for sodium ion batteries, and the direct combustion treatment of phenazines has an environmental impact.
By using the 2H phenazine polymer as the positive electrode material, combining conductive agents and binders, the preparation process includes uniform mixing, coating and drying of the slurry, assembled into a sodium ion half-cell or full cell.
It realizes the efficient application of 2H phenazine polymer in sodium ion batteries, has excellent electrochemical properties, including high capacity retention, specific capacity and cycle stability, solves environmental pollution problems and realizes resource recycling.
Smart Images

Figure CN119890459A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion batteries, and in particular relates to a preparation process of a sodium ion battery using a 2H phenazine polymer as a positive electrode material. Background Art
[0002] Phenazine is one of the main by-products in the process of synthesizing 4-aminodiphenylamine. Its direct combustion treatment every year causes it to emit a certain amount of harmful gases and CO2 into the air, which has an impact on the environment to a certain extent.
[0003] Chinese patent CN 113968925 B discloses a 2H phenazine redox polymer, a preparation method and its application in lithium-ion batteries. The 2H phenazine redox polymer (5,10-bis(2-methacryloyloxyethyl)-phenazine) is prepared based on industrial byproduct phenazine and is used as a positive electrode material for lithium-ion batteries. This material exhibits a high working potential (>3V vs. Li / Li + ) and stable cycling performance (capacity retention rate reaches 92% after 200 cycles). However, it is still unclear whether this material can be used in sodium-ion batteries. Summary of the invention
[0004] The present invention is made to solve the above-mentioned problems, and aims to provide a preparation process of a sodium ion battery using a 2H phenazine polymer as a positive electrode material.
[0005] The invention provides a sodium ion battery preparation process using a 2H phenazine polymer as a positive electrode material, which has the following characteristics and comprises the following steps: step 1, preparing a 2H phenazine polymer battery positive electrode material; step 2, mixing the 2H phenazine polymer battery positive electrode material, a conductive agent and a binder in an N-methylpyrrolidone solvent, and mixing them evenly to obtain a slurry 1; step 3, coating the slurry 1 evenly on a current collector aluminum foil, and cutting it into electrode sheets as positive electrode sheets after drying; step 4, assembling the positive electrode sheet with a sodium sheet, a diaphragm, an electrolyte, and a positive and negative electrode shell into a sodium ion half-cell, or assembling the positive electrode sheet with a negative electrode sheet, a diaphragm, a spring, a gasket, an electrolyte, and a positive and negative electrode shell into a sodium ion full battery.
[0006] In the sodium ion battery preparation process using the 2H phenazine polymer as the positive electrode material provided by the present invention, the following characteristics may also be present: wherein, in step 1, the 2H phenazine polymer battery positive electrode material is poly(5,10-bis(2-methacryloyloxyethyl)-phenazine).
[0007] In the sodium ion battery preparation process using the 2H phenazine polymer as the positive electrode material provided by the present invention, the following features may also be present: wherein, in step 1, the preparation process of the 2H phenazine polymer battery positive electrode material comprises:
[0008] Step a1, add phenazine, sodium dithionite, sodium carbonate, and tributylmethylammonium chloride into a round-bottom flask in a molar ratio of 2:3:4:0.8, add acetonitrile and water, and finally add 2-bromoethyl, stir and reflux at 100°C for 48 hours; after the reaction is completed, add water dropwise to the reflux reaction system, then cool to room temperature, filter and wash to obtain a green powder crude product; then recrystallize with methanol to obtain green needle-shaped crystals, and vacuum dry at 100°C to obtain 5,10-bis(2-hydroxyethyl)phenazine BHEP; Step a2, add BHEP and catalyst 4-dimethylaminopyridine into a Shrek bottle in a molar ratio of 2:1, add dichloromethane and triethylamine, stir for three minutes, and Methacryloyl chloride was added dropwise at 0°C for 4 hours. After the reaction was completed, it was extracted with DCM and water, and the organic phase was dried with anhydrous sodium sulfate, rotary evaporated, and then purified by column chromatography to obtain a light yellow solid powder monomer 5,10-bis(2-methacryloyloxyethyl)-phenazine BEMP; step a3, BEMP and initiator AIBN were added into a Shrek bottle at a molar ratio of 246:37, tetrahydrofuran solvent was added, and stirred at 60°C for 24 hours; after the reaction was completed, the residue was dissolved with chloroform, rotary evaporated, and then washed three times with methanol and acetone respectively, centrifuged to obtain a precipitate, and vacuum dried at 80°C to obtain poly(5,10-bis(2-methacryloyloxyethyl)-phenazine) PBEMP.
[0009] In the sodium ion battery preparation process using the 2H phenazine polymer as the positive electrode material provided by the present invention, the following characteristics can also be present: wherein, in step a1, 40 mL of acetonitrile and 10 mL of water are added, the molar ratio of phenazine to 2-bromoethanol is 1:5, and in step a2, the molar ratio of BHEP to triethylamine and methacryloyl chloride is 1:3:3.
[0010] In the sodium ion battery preparation process using the 2H phenazine polymer as the positive electrode material provided by the present invention, the following characteristics can also be present: wherein, in step 2, the conductive agent is multi-walled carbon nanotubes or acetylene black, and the 2H phenazine polymer battery positive electrode material, the conductive agent, and the adhesive are mixed in a mass ratio of 5:4:1.
[0011] In the sodium ion battery preparation process using the 2H phenazine polymer as the positive electrode material provided by the present invention, the process may also have the following characteristics: wherein, in step 4, the sodium sheet is prepared in a glove box filled with argon gas.
[0012] In the sodium ion battery preparation process using the 2H phenazine polymer as the positive electrode material provided by the present invention, the following characteristics can also be present: wherein, in step 4, in the sodium ion half-cell, the electrode sheet is used as the positive electrode, the sodium sheet is used as the negative electrode, the diaphragm is a glass fiber diaphragm, and the positive and negative electrode shells are CR-2016.
[0013] In the sodium ion battery preparation process using the 2H phenazine polymer as the positive electrode material provided by the present invention, the following characteristics can also be present: wherein, in step 4, the negative electrode sheet is prepared according to the following steps: step b1, mixing hard carbon, a conductive agent, and a binder in an N-methylpyrrolidone solvent, and mixing them evenly to obtain slurry 2; step b2, uniformly coating the slurry 2 on the current collector copper foil, and cutting it into electrode sheets as negative electrode sheets after drying.
[0014] In the sodium ion battery preparation process using the 2H phenazine polymer as the positive electrode material provided by the present invention, the following characteristics may also be present: wherein, in step a1, the conductive agent is acetylene black, and the hard carbon, the conductive agent, and the adhesive are mixed in a mass ratio of 8:1:1.
[0015] In the sodium ion battery preparation process using the 2H phenazine polymer as the positive electrode material provided by the present invention, the following characteristics can also be present: wherein, in step 4, in the sodium ion full battery, the electrode sheet is used as the positive electrode, the negative electrode sheet is used as the negative electrode, the diaphragm is a glass fiber diaphragm, the size of the spring is 15.4*1.1mm, the size of the gasket is 15.8*1.0mm, and the positive and negative electrode shells are CR-2032.
[0016] Beneficial effects of the present invention:
[0017] The present invention applies the dihydrophenazine polymer positive electrode material synthesized from industrial waste phenazine as raw material to sodium ion batteries, thereby solving the environmental problems caused by direct incineration of phenazine waste and realizing resource recycling. The preparation process of sodium ion batteries is simple. The positive electrode made of the dihydrophenazine polymer positive electrode material has excellent electrochemical performance in sodium ion batteries, has high capacity retention rate and specific capacity, exhibits excellent cycle stability, and has a high average redox potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Attached Figure 1 The cycle curves of the sodium ion half-cell of the poly (5,10-bis (2-methacryloyloxyethyl) -phenazine) cathode material provided by the embodiment of the present invention in three fluoroethylene carbonate (FEC) ester electrolyte systems without additives are shown;
[0019] Attached Figure 2 The cycle curve of the sodium ion half-cell of the poly (5,10-bis (2-methacryloyloxyethyl) -phenazine) positive electrode material provided by the embodiment of the present invention in the ester electrolyte with different sodium salts but with the additive FEC added is shown.
[0020] Attached Figure 3 The cycle curve of the sodium ion half-cell of poly (5,10-bis (2-methacryloyloxyethyl) -phenazine) cathode material in ether electrolyte;
[0021] Attached Figure 4 The cyclic voltammetry curve of the sodium ion half-cell of poly (5,10-bis (2-methacryloyloxyethyl) -phenazine) cathode material in 1M NaPF6-PC + FEC (5%, vol%) electrolyte;
[0022] Attached Figure 5 Cyclic voltammetry curve of sodium ion half cell of poly (5,10-bis (2-methacryloyloxyethyl) -phenazine) cathode material in 1M NaPF6-DEGDME electrolyte.
[0023] Attached Figure 6 This is the cycling curve of the sodium ion full battery with poly (5,10-bis (2-methacryloyloxyethyl) -phenazine) positive electrode material in acetylene black (AB) as the conductive agent and 1M NaPF6-PC-EC electrolyte. DETAILED DESCRIPTION
[0024] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following examples and drawings specifically illustrate the preparation process of sodium ion batteries using the 2H phenazine polymer of the present invention as the positive electrode material.
[0025] Example
[0026] This embodiment provides a sodium ion battery preparation process using 2H phenazine polymer as a positive electrode material, and the specific method includes the following steps:
[0027] Step 1: prepare a 2H phenazine polymer battery positive electrode material. The 2H phenazine polymer battery positive electrode material is poly (5,10-bis (2-methacryloyloxyethyl) -phenazine).
[0028] The preparation process of poly (5,10-bis (2-methacryloyloxyethyl) -phenazine) is as follows:
[0029] Step a1, add substrate phenazine (3.600 g, 20 mmol), sodium dithionite (5.218 g, 30 mmol), sodium carbonate (4.235 g, 40 mmol), and tributylmethylammonium chloride (1.885 g, 8 mmol) into a 500 mL two-necked round-bottom flask. Under nitrogen purge, 40 mL of acetonitrile and 10 mL of water were added, and finally 2-bromoethanol (12.482 g, 100 mmol) was added, and the mixture was stirred and refluxed at 100°C for 48 h. After the reaction was completed, 100 mL of water was added dropwise to the reflux reaction system, and then cooled to room temperature, filtered with a Buchner funnel, and the filter cake was washed with an appropriate amount of water to obtain a green powder crude product. It was then recrystallized with methanol to obtain green needle-shaped crystals, and vacuum dried at 100°C to obtain 5,10-bis(2-hydroxyethyl)phenazine (BHEP) (2.452 g, 13.62 mmol), with a yield of 45.4%. 1H NMR (400 MHz, DMSO-d6): δ4.92 (s, 2H), 3.57 (q, 8H).
[0030] Step a2, add the substrate BHEP (0.400 g, 1.48 mmol) and the catalyst 4-dimethylaminopyridine (DMAP) (0.009 g, 0.074 mmol) into a 100 mL Shrek bottle, add 8 mL of dichloromethane and triethylamine (0.449 g, 4.44 mmol) under nitrogen purge and stir for three minutes, add methacryloyl chloride (0.464 g, 4.44 mmol) dropwise at 0°C and react for 4 hours. After the reaction is completed, extract with DCM and water, dry the organic phase with anhydrous sodium sulfate, rotary evaporate, and then purify by column chromatography (eluent DCM) to obtain a light yellow solid powder monomer 5,10-bis(2-methacryloyloxyethyl)-phenazine (BEMP) with a yield of 51%. 1 H NMR (400MHz, DMSO-d6): δ5.99(s,2H),5.67(s,2H),4.28(s,4H),3.33(t,4H),1.84(s,6H).
[0031] Step a3, add substrate BEMP (0.1 g, 0.246 mmol) and initiator AIBN (0.006 g, 0.037 mmol) into a 10 mL Shrek bottle, add tetrahydrofuran solvent (1 mL) under nitrogen purge, and stir at 60 ° C for 24 h; after the reaction, dissolve the residue with chloroform, rotary evaporate, and then wash with methanol and acetone three times respectively, centrifuge to obtain a precipitate, and vacuum dry at 80 ° C to obtain poly (5,10-bis (2-methacryloyloxyethyl) - phenazine) (PBEMP) (75.2 mg, 0.185 mmol), with a yield of 75.2%.
[0032] Step 2: Prepare the positive electrode.
[0033] The 2H phenazine polymer battery positive electrode material, the conductive agent multi-walled carbon nanotube (or acetylene black) and the binder (PVDF) were mixed in a mass ratio of 5:4:1, ball-milled for 2 hours, and the slurry was evenly coated on the aluminum foil current collector with a coater at a thickness of 200 μm, dried at 80°C under vacuum for 12 hours, and sliced to obtain a positive electrode sheet. The diameter of the positive electrode sheet is 14 mm.
[0034] Step three: prepare the negative electrode sheet.
[0035] 3.1 Preparation of negative electrode sheet for sodium ion half-cell
[0036] In a glove box filled with argon (H2O < 0.01ppm, O2 < 0.01ppm), use a ceramic knife to cut the sodium into small blocks and put them into a ziplock bag. Then grind them into sodium sheets with a thickness of about 1.5mm. Use a cutting knife to cut them into sodium discs with a diameter of 14mm as sodium negative electrode sheets for later use.
[0037] 3.2 Preparation of negative electrode sheets for sodium ion full batteries
[0038] Hard carbon (commercially purchased), conductive agent Super-P and binder (PVDF) were mixed in a mass ratio of 8:1:1. After ball milling for 2 hours, the slurry was evenly coated on the copper foil current collector with a coater at a thickness of 200 μm. The mixture was dried at 80°C under vacuum for 12 hours and sliced to obtain a carbon negative electrode sheet for later use.
[0039] Step 4: Prepare a sodium ion battery. The sodium ion battery is a sodium ion half-cell or a sodium ion full-cell.
[0040] 4.1 Assembly of Na-ion half-cell
[0041] 1M NaPF6-EC / DEC / DMC (v / v / v=1:1:1) (or 1M NaPF6-PC, or 1M NaPF6-PC / EC (v / v=1:1), 1M NaPF6-PC+FEC (5%, vol%), 1M NaClO4-PC+FEC (5%, vol%) and 1M NaPF6-DEGDME were used as electrolytes, and the separator was a glass fiber separator (Celgard2500). The battery was packaged into a CR2016 button battery using a sealing machine in the order of positive electrode shell, positive electrode sheet (working electrode), separator, sodium negative electrode sheet, nickel foam and negative electrode shell.
[0042] 4.5 Assembly of sodium-ion full batteries
[0043] Using 1M NaPF6-PC / EC (v / v=1:1) as the electrolyte and a glass fiber separator (Celgard2500), the battery was assembled into a CR2032 button battery using a sealing machine in the order of negative electrode shell, spring (specification 15.4*1.1mm), gasket (specification 15.8*1.0mm), carbon negative electrode sheet, separator, positive electrode sheet, and positive electrode shell.
[0044] The electrochemical performance of the assembled sodium ion battery was tested.
[0045] Figure 1 The cycling curves of sodium ion half-cells of poly (5,10-bis (2-methacryloyloxyethyl) -phenazine) cathode materials in three fluoroethylene carbonate (FEC) ester electrolyte systems without additives.
[0046] from Figure 1 It can be seen that the positive electrode material of this embodiment has good cycle stability. After three cycles of activation, the specific capacity in 1M NaPF6-PC / EC (v / v=1:1) electrolyte is the highest, with an initial capacity of 144 mA hg -1 (Theoretical capacity 132mA hg -1 , including the capacity contribution of carbon nanotubes), the capacity is still 111mA hg after 200 cycles -1 (84% of theoretical capacity) and high cycle stability.
[0047] Attached Figure 2 This is the cycling curve of the sodium ion half-cell of poly (5,10-bis (2-methacryloyloxyethyl) -phenazine) positive electrode material in ester electrolyte with different sodium salts but with the additive FEC added.
[0048] from Figure 2 As can be seen from the figure, the positive electrode material of this embodiment is 0.2Ag -1 At a current density of , compared with NaClO4 sodium salt, this NaPF6 has a higher specific capacity, and the addition of FEC improves the activation process required for the battery and solves the problem of initial instability in ester batteries.
[0049] Attached Figure 3 This is the cycling curve of the sodium ion half-cell of poly (5,10-bis (2-methacryloyloxyethyl) -phenazine) positive electrode material in ether electrolyte.
[0050] from Figure 3 It can be seen that the positive electrode material of this embodiment has a wide voltage range of 1.5-4.2V and a sodium ion half-cell in an ether electrolyte. -1 At a current density of 1.5 Hz, about 97 mA hg was achieved after 150 cycles. -1The discharge specific capacity also solves the problem of initial instability.
[0051] Attached Figure 4 Cyclic voltammetry curve of sodium ion half-cell of poly (5,10-bis (2-methacryloyloxyethyl) -phenazine) cathode material in 1M NaPF6-PC + FEC (5%, vol%) electrolyte.
[0052] from Figure 4 It can be seen that the positive electrode material of this embodiment exhibits two pairs of redox peaks in the sodium ion half-cell in 1M NaPF6-PC+FEC (5%, vol%) electrolyte in the voltage range of 1.5V-4.3V, which are 2.52 / 3.16V and 3.48 / 3.93V, respectively, corresponding to the two-step redox reactions of the positive electrode material.
[0053] Attached Figure 5 Cyclic voltammetry curve of sodium ion half cell of poly (5,10-bis (2-methacryloyloxyethyl) -phenazine) cathode material in 1M NaPF6-DEGDME electrolyte.
[0054] from Figure 5 It can be seen that the cathode material of this embodiment exhibits two pairs of redox peaks in the sodium ion half-cell in 1M NaPF6-DEGDME electrolyte in the voltage range of 1.5V-4.3V, which are 3.03 / 3.12V and 3.85 / 3.95V, respectively, corresponding to the two-step redox reactions of the cathode material.
[0055] Attached Figure 6 This is the cycling curve of the sodium ion full battery with poly (5,10-bis (2-methacryloyloxyethyl) -phenazine) positive electrode material in acetylene black as the conductive agent and 1M NaPF6-PC-EC electrolyte.
[0056] like Figure 6 As shown, the sodium ion full battery of this embodiment is -1 The initial capacity is 100 mA hg -1 (Theoretical capacity 76%), first cycle coulomb efficiency 86%, cycle 100 cycles still about 95mA hg -1 The discharge capacity.
[0057] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A process for preparing a sodium ion battery using a 2H phenazine polymer as a positive electrode material, characterized in that: The following steps are involved: Step 1, preparing a 2H phenazine polymer battery positive electrode material; Step 2, mixing the 2H phenazine polymer battery positive electrode material, conductive agent, and binder in N-methylpyrrolidone solvent, and mixing evenly to obtain slurry 1; Step 3, uniformly coating the slurry 1 on the current collector aluminum foil, and cutting into electrode sheets as positive electrode sheets after drying; Step 4, assembling the positive electrode sheet with the sodium sheet, the diaphragm, the electrolyte, and the positive and negative electrode shells into a sodium ion half-cell, or assembling the positive electrode sheet with the negative electrode sheet, the diaphragm, the spring, the gasket, the electrolyte, and the positive and negative electrode shells into a sodium ion full battery.
2. The process for preparing a sodium ion battery using the 2H phenazine polymer as a positive electrode material according to claim 1, characterized in that: in, In step 1, the 2H phenazine polymer battery positive electrode material is poly (5,10-bis (2-methacryloyloxyethyl) -phenazine).
3. A process for preparing a sodium ion battery using the 2H phenazine polymer as a positive electrode material according to claim 2, Features: Wherein, in step 1, the preparation process of the 2H phenazine polymer battery positive electrode material includes: Step a1, adding phenazine, sodium dithionite, sodium carbonate, and tributylmethylammonium chloride into a round-bottom flask in a molar ratio of 2:3:4:0.8, adding acetonitrile and water, and finally adding 2-bromoethyl, stirring and reflux at 100° C. for 48 hours; after the reaction is completed, adding water dropwise to the reflux reaction system, then cooling to room temperature, filtering and washing to obtain a green powder crude product; then recrystallizing with methanol to obtain green needle-shaped crystals, and vacuum drying at 100° C. to obtain 5,10-bis(2-hydroxyethyl)phenazine BHEP; Step a2, adding the BHEP and the catalyst 4-dimethylaminopyridine into a Shrek bottle at a molar ratio of 20:1, adding dichloromethane and triethylamine and stirring for three minutes, adding methacryloyl chloride dropwise at 0°C and reacting for 4 hours, after the reaction is completed, extracting with DCM and water, drying the organic phase with anhydrous sodium sulfate, rotary evaporation, and then purifying by column chromatography to obtain a light yellow solid powder monomer 5,10-bis(2-methacryloyloxyethyl)-phenazine BEMP; Step a3, adding the BEMP and initiator AIBN into a Shrek bottle at a molar ratio of 246:37, adding tetrahydrofuran solvent, and stirring at 60° C. for 24 hours; after the reaction is completed, dissolving the residue with chloroform, rotary evaporation, and then washing with methanol and acetone three times respectively, centrifuging to obtain a precipitate, and vacuum drying at 80° C. to obtain poly(5,10-bis(2-methacryloyloxyethyl)-phenazine) PBEMP.
4. The process for preparing a sodium ion battery using the 2H phenazine polymer as a positive electrode material according to claim 3, characterized in that: in, In step a1, 40 mL of acetonitrile and 10 mL of water were added, and the molar ratio of phenazine to 2-bromoethanol was 1:
5. In step a2, the molar ratio of BHEP to triethylamine and methacryloyl chloride is 1:3:
3.
5. The process for preparing a sodium ion battery using the 2H phenazine polymer as a positive electrode material according to claim 1, characterized in that: in, In step 2, the conductive agent is multi-walled carbon nanotubes or acetylene black, The 2H phenazine polymer battery positive electrode material, the conductive agent, and the adhesive are mixed in a mass ratio of 5:4:
1.
6. The process for preparing a sodium ion battery using the 2H phenazine polymer as a positive electrode material according to claim 1, characterized in that: in, In step 4, the sodium sheet is prepared in a glove box filled with argon.
7. A process for preparing a sodium ion battery using the 2H phenazine polymer as a positive electrode material according to any one of claims 1 to 6, characterized in that: in, In step 4, in the sodium ion half-cell, the electrode sheet is used as the positive electrode, the sodium sheet is used as the negative electrode, the diaphragm is a glass fiber diaphragm, and the positive and negative electrode shells are CR-2016.
8. A process for preparing a sodium ion battery using the 2H phenazine polymer as a positive electrode material according to any one of claims 1 to 6, characterized in that: in, In step 4, the negative electrode sheet is prepared according to the following steps: Step b1, mixing hard carbon, a conductive agent and a binder in an N-methylpyrrolidone solvent, and mixing them evenly to obtain a slurry 2; Step b2, uniformly coating the slurry 2 on the current collector copper foil, and cutting it into electrode sheets as negative electrode sheets after drying.
9. The process for preparing a sodium ion battery using the 2H phenazine polymer as a positive electrode material according to claim 8, characterized in that: in, In step a1, the conductive agent is acetylene black, and the hard carbon, the conductive agent, and the adhesive are mixed in a mass ratio of 8:1:
1.
10. The process for preparing a sodium ion battery using the 2H phenazine polymer as a positive electrode material according to claim 8, characterized in that: in, In step 4, in the sodium ion full battery, the electrode sheet is used as the positive electrode, the negative electrode sheet is used as the negative electrode, the diaphragm is a glass fiber diaphragm, the size of the spring is 15.4*1.1mm, the size of the gasket is 15.8*1.0mm, and the positive and negative electrode shells are CR-2032.
Citation Information
Patent Citations
A 2H phenazine redox polymer, its preparation method, and its application in lithium-ion batteries.
CN113968925B